The Dermis of Millivora Capenesis (American International Journal of Humanities, Arts and Social Sciences, 2019)
The present study was conducted on the dorsal skin of  three (Millivora  Capenesis)., Dermis were collected from  healthy animals,formalin fixed and carried out routein histological procedure,then section at thicness six micrometer and stained by Hematoxylin and Eosin stain .  Histologically,the dermis was composed of the papillary and reticular layers , the papillary layer was formed from loose connective tissue, composed of a bundant collageneous fibers, few elastic fibers, net work of blood capillaries, large artery , large vein and meissner , and pacinian corpscules (tactile corpscules) , the deeper layer of dermis was contain dense connective tissue that included skin appendages such as hair , sebaceous glands , sweat glands , there was two types of hair follicles , primary and secondary follicles , the sebaceous glands which surrounded the hair follicles , these glands were alveolar glands , while sweat glands were simple saccular glands that lined by low cuboidal epithelium from another hand , the ducts of sweat gland was lined by stratified cuboidal epithelium .the meissner corpscule was singly located in the papillary layer of the dermis, while the pacinian corpscule was found in the reticular layers ,our findings were showed these corpscules as onion shapes.The dermis of Millivora Capenesis consist of papillary and reticular layers with skin layer appendage; Sweat gland, sebaceous glands, primary and secondary hair follicles with meissner and pacinian corpscules